KAJIAN KELAYAKAN PERMUKIMAN DI KELURAHAN MAESA UNIMA KECAMATAN TONDANO SELATAN KABUPATEN MINAHASA - Grace Amanda Rammang; Xaverius Erick Lobja; Hermon Maurits Karwur (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2022)
Settlements are not just a place to live, but are developing their functions as psychological, aesthetic, social status, and economic status needs. Therefore, to meet the needs of settlements, it is necessary to standardize the feasibility as a dwelling. This research is intended as a feasibility study for settlements in the Maesa Unima sub-district, South Tondano sub-district, Minahasa district. The method used is qualitative research. The sub-focus in this research are 1) location conditions, 2) infrastructure and facilities conditions, and 3) environmental improvement conditions through reforestation. Informants in this study were people living in Maesa Unima village, representatives of the village government, sub-district government, and district government using purposive sampling and snowball sampling methods. Data collection techniques were carried out through observation, documentation, and interviews. The study results indicate that disaster vulnerability states that settlements in the Maesa Unima sub-district are quite low. The cleanliness of the residential environment is quite clean, but there is still garbage found on the streets. Residential infrastructure and facilities are still lacking in terms of inadequate road conditions, clogged drainage with garbage and soil, access to health services is easy to reach, worship infrastructure is not complete, and it is still difficult to get access to clean water. Regarding the importance of reforestation, public awareness is quite good. The community has carried out reforestation activities by planting their home gardens with vegetables, spices, and shade trees. In general, the residential area in Maesa Unima village has not fully met the standardization as a residence.